2021
DOI: 10.3390/ijms22115812
|View full text |Cite
|
Sign up to set email alerts
|

Role of Receptor Protein Tyrosine Phosphatases (RPTPs) in Insulin Signaling and Secretion

Abstract: Changes in lifestyle in developed countries have triggered the prevalence of obesity and type 2 diabetes mellitus (T2DM) in the latest years. Consequently, these metabolic diseases associated to insulin resistance, and the morbidity associated with them, accounts for enormous costs for the health systems. The best way to face this problem is to identify potential therapeutic targets and/or early biomarkers to help in the treatment and in the early detection. In the insulin receptor signaling cascade, the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…It has been shown that inhibition of PTP1B, a main negative regulator of insulin receptor signaling, can improve glucose homeostasis and insulin signaling ( 131 ). In the insulin receptor signaling cascade, protein tyrosine kinase amplifies the insulin signaling response, and phosphatase is necessary to regulate the rate and duration of the reaction ( 132 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…It has been shown that inhibition of PTP1B, a main negative regulator of insulin receptor signaling, can improve glucose homeostasis and insulin signaling ( 131 ). In the insulin receptor signaling cascade, protein tyrosine kinase amplifies the insulin signaling response, and phosphatase is necessary to regulate the rate and duration of the reaction ( 132 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…Protein tyrosine phosphorylation plays an important role in signal transduction processes involved in cell growth, metabolism, differentiation, and survival [ 1 ]. Protein tyrosine phosphatases (PTPs) along with protein tyrosine kinases control the phosphorylation of tyrosine residues [ 2 ]. PTPs serve as important regulators of signaling events and regulate tyrosine phosphorylation by catalyzing the removal of phosphate groups from phosphorylated tyrosine residues in proteins [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin, a negative regulator of its own signal transduction, downregulates the cell surface receptor when the insulin level increases, which contributes to reduced insulin signal transduction (Haeusler et al, 2018). In vitro studies have found that inhibition of serine/threonine phosphorylation can antagonize or terminate insulin signaling and thus is an important mechanism of IR (Sevillano et al, 2021). In addition, inflammatory cytokines and lipotoxicity can also inhibit phosphorylation (Kalafati et al, 2021;Lyu et al, 2021).…”
Section: Ir and Pcos Endometriummentioning
confidence: 99%